Penetapan Kadar Kalsium Pada Daun Murbei (Morus Alba L.) Secara Kompleksometri - Zulfisa Zulfisa; Lisa Agustin (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2022)
Calcium is one of the essential nutrients that is needed for various body functions. To meet the needs of calcium, the Indonesian people generally still pay attention to the natural products contained therein. Of the many plants, one of the plants that contains calcium is mulberry leaf (Morus alba L.) which is one of the plants that grows a lot in Indonesia. The purpose of this study was to determine the level of calcium contained in mulberry leaves by complexometry. Based on the research that has been done, it can be concluded that mulberry leaves contain calcium of 0.244 % b⁄b calculated as fresh weight.